Conductive particles, conductive material, and connection structure

By placing the conductive portion containing indium on the surface of the substrate particles and heating under specific conditions to achieve melting, the problem of insufficient conduction reliability of conductive particles in the prior art under low temperature environment is solved, and the conduction reliability and hot and cold cycle characteristics of the connecting structure are improved.

CN119604951APending Publication Date: 2025-03-11SEKISUI CHEMICAL CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380058248.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-11-11
Filing Date
2023-11-10
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The existing conductive particles are difficult to show the melting of tin metal in low temperature environments, resulting in insufficient conduction reliability and are prone to peeling off or cracks during the hot and cold cycle.

Method used

The conductive portion arranged on the surface of the substrate particles is composed of indium and heated at 160°C for 1 minute to achieve melting of the conductive portion. In addition, the conductive portion may have an alloy layer including tin and indium, or a layer including copper or nickel to improve the conductivity.

Benefits of technology

The conduction reliability and hot and cold cycle characteristics of the connecting structure are improved, and the stability and durability of conductive particles are ensured.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119604951A_ABST
    Figure CN119604951A_ABST
Patent Text Reader

Abstract

Provided are conductive particles capable of improving conduction reliability and thermal cycle characteristics of the obtained connection structure. This conductive particle has a base particle and a conductive part disposed on the surface of the base particle, the conductive part containing indium, and the conductive part melts when the conductive particle is heated for 1 minute in an atmosphere at 160 DEG C.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to conductive particles comprising substrate particles and a conductive portion disposed on the surface of the substrate particles. In addition, the present invention relates to a conductive material and a bonded structure using the conductive particles. Background Art

[0002] Anisotropic conductive materials such as anisotropic conductive pastes and anisotropic conductive films are widely known. In the anisotropic conductive material, conductive particles are dispersed in a binder resin.

[0003] The anisotropic conductive material is used to obtain various connection structures. Examples of the connection using the anisotropic conductive material include connection between a flexible printed substrate and a glass substrate (FOG (Film on Glass)), connection between a semiconductor chip and a flexible printed substrate (COF (Chip on Film)), connection between a semiconductor chip and a glass substrate (COG (Chipon Glass)), and connection between a flexible printed substrate and a glass epoxy substrate (FOB (Film on Board)).

[0004] In recent years, the miniaturization and lightness of devices using connection structures have been continuously developed. As a result, the conductive particles used in the connection structures are required to have high conductivity such as large capacity and low resistance. As the conductive particles, tin particles are sometimes used that can improve the conductivity by joining with electrodes through metal melting.

[0005] The following patent document 1 discloses conductive particles having substrate particles and a metal coating layer coating the substrate particles. In the conductive particles, the metal coating layer includes an inner copper plating layer and an outer tin plating layer that have been subjected to chemical plating. In the conductive particles, the tin plating layer is formed by a chemical tin plating bath containing a reducing agent. In the conductive particles, the film thickness of the copper plating layer is 0.040 μm or more, the film thickness of the tin plating layer is 0.050 μm or more, and the total value of the film thickness of the copper plating layer and the film thickness of the tin plating layer is 0.090 μm or more and 0.180 μm or less.

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: Japanese Patent Application Publication No. 2011-134480 Summary of the invention

[0009] Technical problem to be solved by the invention

[0010] In recent years, in order to reduce the burden on the substrate and the like, mounting is sometimes performed in a low temperature environment of less than 200°C.

[0011] However, for the conductive particles described in Patent Document 1, i.e., conductive particles having a two-layer structure in which the conductive portion has a tin layer on the outside, it is difficult to exhibit tin metal melting under installation conditions below 200° C., and when preparing a connection structure by electrically connecting electrodes, there is a technical problem that the conduction reliability cannot be sufficiently improved (the connection resistance cannot be sufficiently reduced).

[0012] In addition, in a connection structure prepared using conventional conductive particles, when cooling and heating are repeated, the conductive particles may be peeled off from the substrate or cracks may be generated in the conductive particles. That is, conventional conductive particles have a technical problem that it is difficult to improve the thermal cycling characteristics of the obtained connection structure.

[0013] An object of the present invention is to provide conductive particles capable of improving the conduction reliability and thermal cycle characteristics of a connection structure obtained. Another object of the present invention is to provide a conductive material and a connection structure using the conductive particles.

[0014] Solutions to technical problems

[0015] According to a broad aspect of the present invention, there is provided a conductive particle having a substrate particle and a conductive portion disposed on a surface of the substrate particle, wherein the conductive portion contains indium and melts when the conductive particle is heated at 160° C. for 1 minute in an air atmosphere.

[0016] According to a specific aspect of the conductive particle according to the present invention, the conductive portion has an alloy layer containing an alloy of tin and indium.

[0017] According to a specific aspect of the conductive particle according to the present invention, the conductive portion has a conductive layer having a melting point of 200° C. or lower, and a content of the conductive layer having a melting point of 200° C. or lower is 10% by weight or more in 100% by weight of the conductive portion.

[0018] According to a specific aspect of the conductive particle according to the present invention, the conductive portion has a layer containing copper or nickel, and the substrate particles are in contact with the layer containing copper or nickel.

[0019] According to a specific aspect of the conductive particle according to the present invention, the layer containing copper or nickel has a thickness of 0.05 μm or more and 2 μm or less.

[0020] According to a specific aspect of the conductive particle according to the present invention, the conductive portion contains tin, and a content of tin in 100% by weight of the conductive portion is 2% by weight or more.

[0021] According to a specific aspect of the conductive particle according to the present invention, the conductive portion has a plurality of protrusions on the outer surface thereof.

[0022] According to a specific aspect of the conductive particle of the present invention, when an X-ray diffraction spectrum of the conductive portion is measured, peaks exist in a region of 32° to 34° and a region of 55.5° to 57.5°.

[0023] According to a specific aspect of the conductive particle according to the present invention, the outer surface of the conductive portion is surface-treated with a flux.

[0024] According to a specific aspect of the conductive particles according to the present invention, the particle diameter of the substrate particles is 0.5 μm or more and 100 μm or less.

[0025] According to a broad aspect of the present invention, there is provided a conductive material including the conductive particles and a binder resin.

[0026] According to a broad aspect of the present invention, there is provided a connection structure comprising: a first connection object component having a first electrode on a surface; a second connection object component having a second electrode on a surface; and a connection portion that connects the first connection object component and the second connection object component, wherein the material of the connection portion includes the conductive particles, and the first electrode and the second electrode are electrically connected via the conductive particles.

[0027] Effects of the Invention

[0028] The conductive particles of the present invention have a substrate particle and a conductive portion disposed on the surface of the substrate particle. In the conductive particles of the present invention, the conductive portion contains indium, and when the conductive particles are heated at 160° C. for 1 minute in an air atmosphere, the conductive portion melts. In the conductive particles of the present invention, since they have the above-mentioned structure, the conduction reliability and thermal cycling characteristics of the obtained connection structure can be improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] [ Figure 1 ] Figure 1 This is a cross-sectional view showing the conductive particles according to the first embodiment of the present invention.

[0030] [ Figure 2 ] Figure 2 This is a cross-sectional view showing conductive particles according to a second embodiment of the present invention.

[0031] [ Figure 3 ] Figure 3 This is a cross-sectional view showing conductive particles according to a third embodiment of the present invention.

[0032] [ Figure 4 ] Figure 4 This is a cross-sectional view showing conductive particles according to a fourth embodiment of the present invention.

[0033] [ Figure 5 ] Figure 5 This is a cross-sectional view schematically showing a connection structure using conductive particles according to the first embodiment of the present invention. DETAILED DESCRIPTION

[0034] Hereinafter, the present invention will be described in detail.

[0035] (Conductive particles)

[0036] The conductive particles of the present invention have substrate particles and a conductive portion disposed on the surface of the substrate particles. In the conductive particles of the present invention, the conductive portion contains indium, and when the conductive particles are heated at 160° C. for 1 minute in an atmospheric atmosphere, the conductive portion melts. In the conductive particles of the present invention, since they have the above-mentioned structure, when the electrodes are electrically connected, the conductive portion melts, and the conduction reliability can be improved. That is, the conduction reliability between the upper and lower electrodes to be connected can be improved. In addition, since the conductive portion melts rapidly, the insulation reliability between the lateral electrodes that cannot be connected can also be ensured.

[0037] In addition, in the conductive particles of the present invention, since the conductive portion containing indium is very soft and ductile, even when cooling and heating are repeated and the substrate is repeatedly expanded or contracted, the conductive particles can be prevented from peeling off from the substrate or cracks can be prevented from being generated in the conductive particles (improving the thermal cycling characteristics of the resulting connected structure).

[0038] In addition, in this specification, "the conductive portion is melted" means that at least a surface portion of the conductive portion is melted.

[0039] Hereinafter, specific embodiments of the present invention will be described with reference to the accompanying drawings.

[0040] Figure 1 This is a cross-sectional view showing the conductive particles according to the first embodiment of the present invention.

[0041] Figure 1 The conductive particles 1 shown have substrate particles 2 and conductive parts 3 arranged on the surfaces of the substrate particles 2. The conductive parts 3 cover the surfaces of the substrate particles 2. The conductive particles 1 are coated particles in which the surfaces of the substrate particles 2 are coated with the conductive parts 3.

[0042] In the conductive particle 1 , the conductive portion 3 is a single-layer conductive layer.

[0043] In the conductive particle 1, the conductive portion 3 contains indium. In the conductive particle 1, when the conductive particle 1 is heated under the condition of 160°C in an air atmosphere for 1 minute, the conductive portion 3 melts.

[0044] In the conductive particle 1 , the conductive portion 3 may be an alloy layer containing an alloy of two or more metals.

[0045] Figure 2 This is a cross-sectional view showing conductive particles according to a second embodiment of the present invention.

[0046] Figure 2 The conductive particles 11 shown have substrate particles 2 and conductive parts 13 disposed on the surfaces of the substrate particles 2. The conductive parts 13 cover the surfaces of the substrate particles 2. The conductive particles 11 are coated particles in which the surfaces of the substrate particles 2 are coated with the conductive parts 13.

[0047] In the conductive particle 11, the conductive part 13 is a conductive layer having a two-layer structure. The conductive part 13 has a first conductive part 13A and a second conductive part 13B. The first conductive part 13A is arranged on the surface of the substrate particle 2. The first conductive part 13A is in contact with the substrate particle 2. The first conductive part 13A is arranged between the substrate particle 2 and the second conductive part 13B. The second conductive part 13B is arranged on the surface of the first conductive part 13A. The second conductive part 13B is in contact with the first conductive part 13A. The second conductive part 13B is the outermost conductive part in the conductive particle 11.

[0048] In the conductive particle 11, the conductive part 13 contains indium. In the conductive particle 11, the first conductive part 13A may contain indium, and the second conductive part 13B may contain indium. In the conductive particle 11, when the conductive particle 11 is heated at 160°C for 1 minute in an air atmosphere, the conductive part 13 melts.

[0049] In the conductive particle 11, the conductive portion 13 may include an alloy layer including an alloy of two or more metals. In the conductive particle 11, the first conductive portion 13A may be an alloy layer including an alloy of two or more metals, and the second conductive portion 13B may be an alloy layer including an alloy of two or more metals.

[0050] Figure 3 This is a cross-sectional view showing conductive particles according to a third embodiment of the present invention.

[0051] Figure 3 The conductive particles 21 shown have substrate particles 2 and conductive parts 23 disposed on the surfaces of the substrate particles 2. The conductive parts 23 cover the surfaces of the substrate particles 2. The conductive particles 21 are coated particles in which the surfaces of the substrate particles 2 are coated with the conductive parts 23.

[0052] In the conductive particle 21, the conductive part 23 is a conductive layer having a three-layer structure. The conductive part 23 has a first conductive part 23A, a second conductive part 23B, and a third conductive part 23C. The first conductive part 23A is arranged on the surface of the substrate particle 2. The first conductive part 23A is in contact with the substrate particle 2. The first conductive part 23A is arranged between the substrate particle 2 and the second conductive part 23B. The second conductive part 23B is arranged on the surface of the first conductive part 23A. The second conductive part 23B is in contact with the first conductive part 23A. The second conductive part 23B is arranged between the first conductive part 23A and the third conductive part 23C. The third conductive part 23C is arranged on the surface of the second conductive part 23B. The third conductive part 23C is in contact with the second conductive part 23B. The third conductive part 23C is the outermost conductive part in the conductive particle 21.

[0053] In the conductive particle 21, the conductive part 23 contains indium. In the conductive particle 21, the first conductive part 23A may contain indium, the second conductive part 23B may contain indium, and the third conductive part 23C may contain indium. In the conductive particle 21, when the conductive particle 21 is heated at 160°C for 1 minute in an air atmosphere, the conductive part 23 melts.

[0054] In the conductive particle 21, the conductive portion 23 may include an alloy layer including an alloy of two or more metals. In the conductive particle 21, the first conductive portion 23A may be an alloy layer including an alloy of two or more metals, the second conductive portion 23B may be an alloy layer including an alloy of two or more metals, and the third conductive portion 23C may be an alloy layer including an alloy of two or more metals.

[0055] Figure 4 This is a cross-sectional view showing conductive particles according to a fourth embodiment of the present invention.

[0056] Figure 4 The conductive particles 31 shown include a substrate particle 2 , a conductive portion 33 disposed on the surface of the substrate particle 2 , a plurality of core substances 34 , and a plurality of insulating substances 35 .

[0057] In the conductive particles 31, the conductive part 33 is a single-layer conductive layer. In the conductive particles, the conductive part may cover the entire surface of the substrate particles or a part thereof. In the conductive particles, the conductive part may be a single-layer conductive layer or a multi-layer conductive layer composed of two or more layers.

[0058] The conductive particles 31 (particularly the conductive part 33) have a plurality of protrusions 33a on the surface. A plurality of core materials 34 are arranged on the surface of the substrate particles 2. A plurality of core materials 34 are embedded in the conductive part 33. The core materials 34 are arranged on the inner side of the protrusions 33a. The conductive part 33 covers the plurality of core materials 34. The outer surface of the conductive part 33 is raised by the plurality of core materials 34 to form protrusions 33a.

[0059] The conductive particles 31 have an insulating substance 35 disposed on the outer surface of the conductive portion 33. At least a portion of the outer surface of the conductive portion 33 is covered with the insulating substance 35. The insulating substance 35 is formed of an insulating material and is an insulating particle. Therefore, the conductive particles of the present invention may also have an insulating substance disposed on the outer surface of the conductive portion. However, the conductive particles of the present invention do not necessarily have to have an insulating substance.

[0060] In the conductive particles 31 , the conductive portion 33 contains indium. In the conductive particles 31 , in this case, when the conductive particles 31 are heated under the condition of 160° C. in the air atmosphere for 1 minute, the conductive portion 33 melts.

[0061] In the conductive particles 31 , the conductive portion 33 may be an alloy layer containing an alloy of two or more metals.

[0062] Hereinafter, other details of the conductive particles will be described.

[0063] In the present specification, "(meth)acrylate" means acrylate and methacrylate. "(meth)acrylic" means acrylic and methacrylic. "(meth)acryloyl" means acryloyl and methacryloyl.

[0064] The particle size of the conductive particles is preferably 0.8 μm or more, more preferably 3 μm or more, further preferably 5 μm or more, preferably 105 μm or less, more preferably 50 μm or less, further preferably 40 μm or less. When the particle size of the conductive particles is above the lower limit and below the upper limit, conduction reliability and insulation reliability can be improved.

[0065] The particle size of the conductive particles is preferably an average particle size, which represents a number average particle size. The particle size of the conductive particles can be obtained, for example, by observing 50 arbitrary conductive particles with an electron microscope or an optical microscope and calculating the average particle size of each conductive particle; or by performing laser diffraction particle size distribution measurement.

[0066] From the viewpoint of further effectively exerting the effect of the present invention, the coefficient of variation (CV value) of the particle size of the conductive particles is preferably 10% or less, more preferably 5% or less. The lower limit of the coefficient of variation (CV value) of the particle size of the conductive particles is not particularly limited. The coefficient of variation (CV value) of the particle size of the conductive particles may be 0% or more, or 1% or more.

[0067] The coefficient of variation (CV value) can be determined as follows.

[0068] CV value (%) = (ρ / Dn) × 100

[0069] ρ: Standard deviation of particle size of conductive particles

[0070] Dn: average value of particle size of conductive particles

[0071] The shape of the conductive particles is not particularly limited, and the conductive particles may be spherical, may be other than spherical, and may be flat.

[0072] From the viewpoint of further suppressing the occurrence of cracks during stress loading, the 10% K value of the conductive particles is preferably 500 N / mm 2 More preferably 1000 N / mm 2 Above, preferably 17000N / mm 2 Below, more preferably 13000N / mm 2 the following.

[0073] The 10% K value of the conductive particles can be measured, for example, as follows.

[0074] Using a micro compression tester, the conductive particles are compressed under the condition of applying a maximum test load of 60mN for 20 seconds at 25°C on the smooth indenter end face of a cylinder (diameter 50μm, diamond). The load value (N) and compression displacement (mm) at this time are measured. According to the obtained measured values, the 10%K value (compression elastic modulus) can be obtained by the following formula. As the micro compression tester, for example, "Fischer Scope H-100" made by Fischer Company is used.

[0075] 10%K value (N / mm 2 )=(3 / 2 1 / 2 )·F·S -3 / 2 ·R -1 / 2

[0076] F: Load value when conductive particles are compressed by 10% (N)

[0077] S: Compression displacement when the conductive particles are compressed by 10% (mm)

[0078] R: Radius of conductive particles (mm)

[0079] The conductive particles are preferably used to obtain a conductive material by being dispersed in a binder resin.

[0080] <Base particles>

[0081] As the substrate particles, resin particles, inorganic particles other than metal particles, organic-inorganic hybrid particles and metal particles can be cited. The substrate particles are preferably substrate particles other than metal particles, more preferably resin particles, inorganic particles other than metal particles or organic-inorganic hybrid particles. The substrate particles can be core-shell particles having a core and a shell disposed on the surface of the core. The core can be an organic core, and the shell can be an inorganic shell.

[0082] As the material of the resin particles, polyolefin resins such as polyethylene, polypropylene, polystyrene, polyvinyl chloride, polyvinylidene chloride, polyisobutylene and polybutadiene can be cited; acrylic resins such as polymethyl methacrylate and polymethyl acrylate; polycarbonate, polyamide, phenol formaldehyde resin, melamine formaldehyde resin, benzoguanamine formaldehyde resin, urea formaldehyde resin, phenolic resin, melamine resin, benzoguanamine resin, urea formaldehyde resin, epoxy resin, unsaturated polyester resin, saturated polyester resin, polyethylene terephthalate, polysulfone, polyphenylene ether, polyacetal, polyimide, polyamideimide, polyetheretherketone, polyethersulfone and divinylbenzene polymers can be cited. The divinylbenzene polymer can be a divinylbenzene copolymer. As the divinylbenzene copolymer, divinylbenzene-styrene copolymer and divinylbenzene-(meth)acrylate copolymer can be cited. Since the hardness of the resin particles can be easily controlled within an appropriate range, the material of the resin particles is preferably a polymer obtained by polymerizing one or more polymerizable monomers having an ethylenically unsaturated group.

[0083] When the resin particles are obtained by polymerizing a polymerizable monomer having an ethylenically unsaturated group, examples of the polymerizable monomer having an ethylenically unsaturated group include non-crosslinking monomers and crosslinking monomers.

[0084] Examples of the non-crosslinking monomer include: styrene monomers such as styrene and α-methylstyrene; carboxyl group-containing monomers such as (meth)acrylic acid, maleic acid, and maleic anhydride; alkyl (meth)acrylate compounds such as methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, lauryl (meth)acrylate, cetyl (meth)acrylate, stearyl (meth)acrylate, cyclohexyl (meth)acrylate, and isobornyl (meth)acrylate; 2-hydroxyethyl (meth)acrylate , (meth)acrylate compounds containing oxygen atoms, such as (meth)acrylate glyceryl, polyoxyethylene (meth)acrylate and glycidyl (meth)acrylate; nitrile-containing monomers such as (meth)acrylonitrile; vinyl ether compounds such as methyl vinyl ether, ethyl vinyl ether and propyl vinyl ether; acid vinyl ester compounds such as vinyl acetate, vinyl butyrate, vinyl laurate and vinyl stearate; unsaturated hydrocarbons such as ethylene, propylene, isoprene and butadiene; halogen-containing monomers such as trifluoromethyl (meth)acrylate, pentafluoroethyl (meth)acrylate, vinyl chloride, vinyl fluoride and chlorostyrene, etc.

[0085] Examples of the crosslinking monomer include tetramethylolmethane tetra(meth)acrylate, tetramethylolmethane tri(meth)acrylate, tetramethylolmethane di(meth)acrylate, trimethylolpropane tri(meth)acrylate, dipentaerythritol hexa(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol poly(meth)acrylate, pentaerythritol tetra(meth)acrylate, glycerol tri(meth)acrylate, glycerol di(meth)acrylate, (poly)ethylene glycol di(meth)acrylate, The crosslinking monomer is preferably a polyfunctional (meth)acrylate compound such as (poly)ethylene glycol di(meth)acrylate, (poly)propylene glycol di(meth)acrylate, (poly)tetramethylene glycol di(meth)acrylate, and 1,4-butanediol di(meth)acrylate; a silane-containing monomer such as triallyl (iso)cyanurate, triallyl trimellitate, divinylbenzene, diallyl phthalate, diallyl acrylamide, diallyl ether, and γ-(meth)acryloyloxypropyl trimethoxysilane, trimethoxysilyl styrene, and vinyl trimethoxysilane. From the viewpoint that the particles containing the flux also maintain their shape at the glass transition temperature of the resin particles, the crosslinking monomer is preferably (poly)ethylene glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, or dipentaerythritol poly(meth)acrylate.

[0086] The resin particles can be obtained by polymerizing the polymerizable monomer having an ethylenically unsaturated group using a known method, such as a method of performing suspension polymerization in the presence of a free radical polymerization initiator, and a method of performing polymerization by swelling the monomer with a free radical polymerization initiator using non-crosslinked seed particles.

[0087] In the case where the substrate particles are inorganic particles other than metal or organic-inorganic hybrid particles, examples of inorganic substances used to form the substrate particles include: silicon dioxide, aluminum oxide, barium titanate, zirconium oxide, and carbon black. The inorganic substance is preferably not a metal. Examples of particles formed from the silicon dioxide include: particles obtained by hydrolyzing a silicon compound having two or more hydrolyzable alkoxysilyl groups to form crosslinked polymer particles, and then firing the particles as needed. Examples of the organic-inorganic hybrid particles include: organic-inorganic hybrid particles formed from a crosslinked alkoxysilyl polymer and an acrylic resin, etc.

[0088] The organic-inorganic hybrid particles are preferably core-shell organic-inorganic hybrid particles having a core and a shell disposed on the surface of the core. The core is preferably an organic core. The shell is preferably an inorganic shell. From the viewpoint of effectively reducing the connection resistance between electrodes, the substrate particles are preferably organic-inorganic hybrid particles having an organic core and an inorganic shell disposed on the surface of the organic core.

[0089] Examples of the material of the organic core include the material of the resin particles described above.

[0090] As the material of the inorganic shell, the inorganic substances mentioned as the material of the substrate particles can be cited. The material of the inorganic shell is preferably silicon dioxide. The inorganic shell is preferably formed by forming a metal alkoxide into a shell-like object on the surface of the core by a sol-gel method and then sintering the shell-like object. The metal alkoxide is preferably a silane alkoxide. The inorganic shell is preferably formed by a silane alkoxide.

[0091] When the substrate particles are metal particles, examples of the metal as a material of the metal particles include silver, copper, nickel, silicon, gold, and titanium.

[0092] The particle size of the substrate particles is preferably 0.5 μm or more, more preferably 9.5 μm or more, preferably 100 μm or less, more preferably 49.95 μm or less, and further preferably 39.95 μm or less. When the particle size of the substrate particles is above the lower limit and below the upper limit, the interval between the electrodes becomes smaller, and even if the thickness of the conductive portion is increased, conductive particles with a small particle size can be obtained. In addition, when the conductive portion is formed on the surface of the substrate particles, the particles are not easy to condense, and it is not easy to form condensed conductive particles.

[0093] The shape of the substrate particles is not particularly limited and may be spherical, or may be other than spherical, or may be flat.

[0094] The particle size of the substrate particles is preferably an average particle size, which represents a number average particle size. The particle size of the substrate particles is obtained using a particle size distribution measuring device or the like. The particle size of the substrate particles is preferably obtained by observing any 50 substrate particles with an electron microscope or an optical microscope and calculating the average value. In the conductive particles, when the particle size of the substrate particles is measured, it can be measured, for example, as follows.

[0095] The conductive particles are added to "TECHNOVIT4000" manufactured by Kulzer Company in such a manner that the content of the conductive particles becomes 30% by weight, and the conductive particles are dispersed to prepare an embedded resin body for inspection containing conductive particles. The cross-section of the conductive particles is cut out using an ion milling device ("IM4000" manufactured by Hitachi High-Technologies Corporation) near the center of the conductive particles (substrate particles) dispersed in the embedded resin body for inspection. Then, using a field emission scanning electron microscope (FE-SEM), the image magnification is set to 1000 times, 50 conductive particles are randomly selected, and the substrate particles of each conductive particle are observed. The particle size of the substrate particles in each conductive particle is measured, and they are arithmetic averaged as the particle size of the substrate particles. The image magnification can be changed to, for example, 100 times according to the particle size of the conductive particles.

[0096] <Core material and protrusions>

[0097] The conductive particles preferably have a plurality of protrusions on the outer surface of the conductive portion. Generally speaking, an oxide film is mostly formed on the surface of the electrode in contact with the conductive particles. When using conductive particles having protrusions on the surface, the oxide film can be effectively removed by the protrusions during conductive connection. Therefore, the electrode is in more reliable contact with the conductive particles, the contact area between the conductive particles and the electrode can be sufficiently increased, and the connection resistance can be more effectively reduced. In addition, when the conductive particles are dispersed in an adhesive and used as a conductive material, the adhesive between the conductive particles and the electrode can be further effectively removed by the protrusions of the conductive particles. Therefore, the contact area between the conductive particles and the electrode can be sufficiently increased, and the connection resistance can be more effectively reduced.

[0098] Methods for forming protrusions on the surface of conductive particles include: a method of attaching a core material to the surface of a substrate particle and then forming a conductive portion by chemical plating; and a method of forming a conductive portion by chemical plating on the surface of a substrate particle, attaching a core material, and then forming a conductive layer by chemical plating.

[0099] As a method for attaching the core material to the surface of the substrate particles, for example, there can be mentioned: adding the core material to the dispersion of the substrate particles, aggregating the core material and attaching it to the surface of the substrate particles by, for example, van der Waals force; and adding the core material to a container containing the substrate particles, a method for attaching the core material to the surface of the substrate particles by mechanical action generated by the rotation of the container, etc. Among them, in order to easily control the amount of the attached core material, it is preferred to aggregate the core material and attach it to the surface of the substrate particles in the dispersion.

[0100] The conductive particles may have a first conductive portion on the surface of the substrate particles, a second conductive portion on the surface of the first conductive portion, and a third conductive portion on the surface of the second conductive portion. A core material may also be attached to the surface of the substrate particles. In this case, it is preferred that the core material is coated with the first conductive portion, the second conductive portion, and the third conductive portion. In addition, the core material may also be attached to the surface of the first conductive portion. In this case, it is preferred that the core material is coated with the second conductive portion and the third conductive portion. In addition, the core material may also be attached to the surface of the second conductive portion. In this case, it is preferred that the core material is coated with the third conductive portion.

[0101] As the material constituting the core material, conductive materials and non-conductive materials can be cited. As the conductive material, for example, conductive non-metals such as metals, metal oxides, graphite, and conductive polymers can be cited. As the conductive polymer, polyacetylene can be cited. As the non-conductive material, silicon dioxide, aluminum oxide, zirconium oxide, etc. can be cited. From the viewpoint of improving conductivity, the material constituting the core material is preferably a metal. The core material is preferably a metal particle.

[0102] Examples of the metal include gold, silver, copper, platinum, zinc, iron, lead, tin, aluminum, cobalt, indium, nickel, chromium, titanium, antimony, bismuth, germanium, and cadmium, and alloys consisting of two or more metals such as tin-lead alloys, tin-copper alloys, tin-silver alloys, tin-lead-silver alloys, and tungsten carbide. Among them, nickel, copper, silver, or gold is preferred. The metal constituting the core material may be the same as or different from the metal constituting the conductive portion (conductive layer).

[0103] The shape of the core material is not particularly limited. The shape of the core material is preferably a block. Examples of the core material include a particle-shaped block, an aggregated block formed by agglomeration of a plurality of fine particles, and an indefinite-shaped block.

[0104] The average height of the plurality of protrusions is preferably 0.001 μm or more, more preferably 0.05 μm or more, preferably 0.9 μm or less, more preferably 0.2 μm or less. When the average height of the protrusions is above the lower limit and below the upper limit, the connection resistance between electrodes can be effectively reduced, and the conduction reliability can be further improved.

[0105] <Conductive Part>

[0106] In the present invention, the conductive particles have a conductive portion on the surface. The conductive portion is arranged on the surface of the substrate particles.

[0107] Examples of the metal constituting the conductive portion include tin, gold, silver, copper, tin, platinum, palladium, zinc, lead, aluminum, cobalt, indium, nickel, chromium, titanium, antimony, bismuth, germanium, and cadmium, and alloys thereof. In addition, tin-doped indium oxide (ITO) may also be used as the metal. The metal may be used alone or in combination of two or more.

[0108] In the conductive particles, the conductive portion includes indium, and when the conductive particles are heated at 160° C. for 1 minute in an air atmosphere, the conductive portion melts.

[0109] In the conductive particles, the conductive portion may be formed of one layer or a plurality of layers. The conductive portion may have a laminated structure of two or more layers. From the viewpoint of further effectively exerting the effect of the present invention, when the conductive portion is formed of a plurality of layers, indium is preferably contained in the outermost layer of the conductive portion.

[0110] In the conductive particles, the conductive portion may include two or more metals having different melting points, three or more metals having different melting points, four or more metals having different melting points, or five or more metals having different melting points. In the conductive particles, the conductive portion may include 10 or less metals having different melting points, five or less metals having different melting points, four or less metals having different melting points, three or less metals having different melting points, or two or less metals having different melting points.

[0111] In the conductive particles, one layer may contain two or more metals with different melting points, three or more metals with different melting points, four or more metals with different melting points, or five or more metals with different melting points. In the conductive particles, one layer may contain 10 or less metals with different melting points, five or less metals with different melting points, four or less metals with different melting points, three or less metals with different melting points, or two or less metals with different melting points. In the conductive particles, one layer may contain one metal (indium only).

[0112] From the viewpoint of making the conductive part melt well, in the conductive particles, the conductive part preferably has an alloy layer comprising an alloy of two or more metals. The alloy layer may include an alloy of two or more metals, an alloy of three or more metals, an alloy of 10 or less metals, or an alloy of 5 or less metals. From the viewpoint of further improving the thermal cycling characteristics of the obtained connection structure, in the conductive particles, the conductive part preferably has an alloy layer comprising an alloy of indium and a metal other than indium, and more preferably has an alloy layer comprising an alloy of tin and indium.

[0113] In the conductive particles, when the conductive portion has an alloy layer comprising an alloy of two or more metals (for example, an alloy layer comprising an alloy of tin and indium), from the viewpoint of further improving the thermal cycling characteristics of the resulting connection structure, the alloy layer comprising an alloy of two or more metals (the alloy layer comprising an alloy of tin and indium) is preferably the outermost layer of the conductive portion.

[0114] The thickness of the alloy layer of the alloy containing tin and indium is preferably 0.001 μm or more, more preferably 0.01 μm or more, further preferably 0.1 μm or more, preferably 0.75 μm or less, more preferably 0.5 μm or less, and further preferably 0.3 μm or less. If the thickness of the alloy layer of the alloy containing tin and indium is above the lower limit and below the upper limit, the thermal cycle characteristics of the obtained connection structure can be further improved. It should be noted that the thickness of the alloy layer of the alloy containing tin and indium is the average thickness of each of the conductive particles.

[0115] The thickness of the alloy layer containing an alloy of tin and indium can be measured by observing a cross section of the conductive particles using a transmission electron microscope (TEM), for example.

[0116] From the viewpoint of further improving the thermal cycling characteristics of the obtained bonded structure, in the conductive particles, the conductive portion preferably does not contain bismuth.

[0117] From the viewpoint of more effectively exerting the effects of the present invention, the content of indium in 100 wt % of the conductive portion in the conductive particles is preferably 5 wt % or more, more preferably 10 wt % or more, further preferably 18 wt % or more, and is preferably 50 wt % or less, more preferably 35 wt % or less, further preferably 25 wt % or less.

[0118] From the viewpoint of further effectively exerting the effect of the present invention, the content of indium in 100% by weight of the layer (indium layer) containing indium in the conductive particle is preferably 10% by weight or more, more preferably 30% by weight or more, and more preferably 44% by weight or more. From the viewpoint of further effectively exerting the effect of the present invention, the content of indium in 100% by weight of the layer (indium layer) containing indium in the conductive particle is preferably 99.9% by weight or less, more preferably 98% by weight or less, and more preferably 95% by weight or less. From the viewpoint of further effectively exerting the effect of the present invention, the content of indium in 100% by weight of the layer (indium layer) containing indium in the conductive particle is further preferably 90% by weight or less, particularly preferably 80% by weight or less, and most preferably 72% by weight or less.

[0119] In the case where the conductive portion has an alloy layer comprising an alloy of tin and indium, the content of indium in 100% by weight of the alloy layer comprising an alloy of tin and indium is preferably 10% by weight or more, more preferably 30% by weight or more, and further preferably 44% by weight or more. In 100% by weight of the alloy layer comprising an alloy of tin and indium, the content of indium is preferably 99.9% by weight or less, more preferably 98% by weight or less, further preferably 95% by weight or less, further preferably 90% by weight or less, particularly preferably 80% by weight or less, and most preferably 72% by weight or less. If the content of indium is above the lower limit and below the upper limit, the effect of the present invention can be further effectively exerted.

[0120] The content of the indium (and other metals) in the conductive portion, the indium layer, and the alloy layer containing an alloy of tin and indium can be measured using a high-frequency inductively coupled plasma emission spectrometer or a fluorescent X-ray analyzer. Examples of the high-frequency inductively coupled plasma emission spectrometer include "ICP-AES" manufactured by Horiba, Ltd., and the like. Examples of the fluorescent X-ray analyzer include "EDX-800HS" manufactured by Shimadzu Corporation, and the like.

[0121] In the conductive particles, when the conductive particles are heated at 160° C. for 1 minute in an atmospheric atmosphere (melting test A), the conductive portion melts. At least the surface portion of the conductive portion melts. The conductive portion preferably melts as a whole. In the conductive particles having a plurality of protrusions on the outer surface of the conductive portion, preferably both the surface portion of the conductive portion having the protrusions and the surface portion of the conductive portion without the protrusions melt.

[0122] [Melting Test A]

[0123] The conductive particles are spread on a Cu plate and heated for 1 minute at 160° C. in an air atmosphere. A cross section of the conductive particles after heating is cut out using a focused ion beam (FIB) using a FIB-SEM. After the cross section is cut out, a molten state of the conductive portion in the conductive particles after heating is observed near a junction between the conductive particles and the Cu plate using an electron microscope (SEM).

[0124] In the conductive particles, the conductive portion preferably melts when the conductive particles are heated at 200° C. for 1 minute in an atmospheric atmosphere (melting test B). In this case, the conductive portion preferably melts at least partially on the surface, and more preferably melts entirely on the surface. In the conductive particles having a plurality of protrusions on the outer surface of the conductive portion, it is preferred that both the surface portion of the conductive portion having the protrusions and the surface portion of the conductive portion having no protrusions melt.

[0125] [Melt test B]

[0126] The conductive particles are spread on a Cu plate and heated at 200° C. for 1 minute in an air atmosphere. A cross section of the conductive particles after heating is cut out using a focused ion beam (FIB) using a FIB-SEM. After the cross section is cut out, a molten state of the conductive portion in the conductive particles after heating is observed near a junction between the conductive particles and the Cu plate using an electron microscope (SEM).

[0127] In the conductive particles, the conductive portion preferably melts when the conductive particles are heated at 135° C. for 1 minute in an atmospheric atmosphere (melting test C). In this case, the conductive portion preferably melts at least partially on the surface, and more preferably melts entirely on the surface. In the conductive particles having a plurality of protrusions on the outer surface of the conductive portion, it is preferred that both the surface portion of the conductive portion having the protrusions and the surface portion of the conductive portion having no protrusions melt.

[0128] [Melting Test C]

[0129] The conductive particles were spread on a Cu plate and heated for 1 minute at 135° C. in an air atmosphere. A cross section of the conductive particles after heating was cut out using a focused ion beam (FIB) using a FIB-SEM. After the cross section was cut out, a molten state of the conductive portion in the conductive particles after heating was observed near a junction between the conductive particles and the Cu plate using an electron microscope (SEM).

[0130] It should be noted that in melting test A, melting test B and melting test C, "the conductive part is melted" means that at least one of the following phenomena (1) and (2) is confirmed. (1) When observed with an electron microscope (SEM), no boundary line is observed near the junction between the conductive particles and the Cu plate (interface portion). (2) In the elemental analysis of SEM-EDX when observing using an electron microscope (SEM), the Cu element diffuses from the Cu plate side to the inside of the conductive particles (especially the conductive part). In addition, when both the phenomenon (1) and the phenomenon (2) are not found (a boundary line is observed along the interface between the conductive particles and the Cu plate, and the Cu element does not diffuse from the Cu plate side to the inside of the conductive particles (especially the conductive part)), it is determined that the "conductive part is not melted". Among them, when the conductive part of the conductive particle contains the Cu element in advance, it is determined that the conductive part is melted according to the phenomenon (1).

[0131] The conductive portion in the conductive particle preferably contains copper or nickel from the viewpoint of making the adhesiveness between the conductive portion and the substrate particle good. The conductive portion in the conductive particle may contain copper or nickel.

[0132] From the viewpoint of making the adhesion between the conductive part and the substrate particle good, the conductive part in the conductive particle preferably has a layer containing copper or nickel. From the viewpoint of making the adhesion between the conductive layer and the substrate particle good, the substrate particle is preferably in contact with the layer containing copper or nickel. From the viewpoint of making the adhesion between the conductive layer and the substrate particle good, the layer containing copper or nickel is preferably the innermost layer of the conductive part. From the viewpoint of making the adhesion between the conductive layer and the substrate particle good, the metal constituting the innermost layer of the conductive part is preferably copper or nickel, more preferably nickel. From the viewpoint of making the adhesion between the conductive layer and the substrate particle good, and from the viewpoint of further effectively exerting the effect of the present invention, it is preferred that the substrate particle is in contact with the layer containing copper or nickel, and the layer containing copper or nickel is in contact with the layer containing indium. From the viewpoint of making the adhesion between the conductive layer and the substrate particle further good, and from the viewpoint of further effectively exerting the effect of the present invention, it is more preferred that the layer containing nickel is in contact with the layer containing nickel and the layer containing indium is in contact with the layer containing nickel. From the viewpoint of more effectively exerting the effects of the present invention, the layer containing indium is preferably an alloy layer containing an alloy of tin and indium.

[0133] The thickness of the layer containing copper or nickel is preferably 0.001 μm or more, more preferably 0.01 μm or more, further preferably 0.05 μm or more, particularly preferably 0.1 μm or more, preferably 2 μm or less, more preferably 1.5 μm or less, further preferably 1 μm or less, and particularly preferably 0.75 μm or less. When the thickness of the layer containing copper or nickel is above the lower limit and below the upper limit, the contact area between the conductive particles and the electrode can be increased, and the conduction reliability can be further improved. It should be noted that the thickness of the layer containing copper or nickel is the average thickness of each of the conductive particles.

[0134] The thickness of the layer containing copper or nickel can be measured by observing the cross section of the conductive particles using a transmission electron microscope (TEM), for example.

[0135] From the viewpoint of increasing the contact area between the conductive particles and the electrode and further improving the conduction reliability, the conductive portion preferably contains tin. From the viewpoint of increasing the contact area with the conductive particles and further improving the conduction reliability, the content of tin in 100% by weight of the conductive portion is preferably 2% by weight or more, more preferably 10% by weight or more, more preferably 16% by weight or more, preferably 50% by weight or less, more preferably 30% by weight or less, and more preferably 22% by weight or less.

[0136] From the viewpoint of increasing the contact area between the conductive particles and the electrode and further improving the conduction reliability, the tin content in 100 wt % of the layer containing tin (tin layer) is preferably 2 wt % or more, more preferably 10 wt % or more, further preferably 18 wt % or more, preferably 90 wt % or less, more preferably 70 wt % or less, further preferably 56 wt % or less.

[0137] The content of the tin (and other metals) in the conductive portion and the tin layer can be measured using a high-frequency inductively coupled plasma emission spectrometer or a fluorescent X-ray analyzer. Examples of the high-frequency inductively coupled plasma emission spectrometer include "ICP-AES" manufactured by Horiba, Ltd., and the like. Examples of the fluorescent X-ray analyzer include "EDX-800HS" manufactured by Shimadzu Corporation, and the like.

[0138] From the viewpoint of further improving the conduction reliability, the conductive part preferably has a conductive layer having a melting point of 200°C or less. The conductive part preferably has a conductive layer having a melting point of 190°C or less, more preferably has a conductive layer having a melting point of 180°C or less, further preferably has a conductive layer having a melting point of 170°C or less, further preferably has a conductive layer having a melting point of 160°C or less, further preferably has a conductive layer having a melting point of 160°C or less. The conductive part further preferably has a conductive layer having a melting point of 155°C or less, particularly preferably has a conductive layer having a melting point of 150°C or less, particularly preferably has a conductive layer having a melting point of 140°C or less, and most preferably has a conductive layer having a melting point of 135°C or less. In the case where the conductive part has the preferred conductive layer, the conduction reliability can be further improved. The conductive part may have only one conductive layer having a melting point of 200°C or less, or may have two or more layers.

[0139] From the viewpoint of improving the bonding and adhesion between the conductive particles and the electrode, the conductive layer having a melting point of 200°C or less is preferably the outer surface layer of the conductive portion. From the viewpoint of improving the bonding and adhesion between the conductive particles and the electrode, the conductive portion is preferably a conductive layer having two or more layers, and the conductive layer having a melting point of 200°C or less is the outermost layer of the conductive portion.

[0140] From the viewpoint of making the conductive part melt well, the content of the conductive layer having a melting point below 200°C in 100% by weight of the conductive part is preferably 1% by weight or more, more preferably 3% by weight or more, further preferably 10% by weight or more, preferably 80% by weight or less, more preferably 50% by weight or less, further preferably 30% by weight or less.

[0141] From the viewpoint of making the conductive part melt well, the conductive part is preferably composed of two or more conductive layers, and the two or more conductive layers are stacked (arranged) in such a way that the melting points of the conductive layers gradually increase from the outer surface toward the inner surface of the conductive part. From the viewpoint of making the conductive part melt well, the conductive part is preferably composed of two or more conductive layers, and the two or more conductive layers are stacked in the order of the lower melting points from the outer surface toward the inner surface of the conductive part. From the viewpoint of making the conductive part melt well, among the two or more adjacent conductive layers, the melting point of the outer conductive layer is preferably lower than the melting point of the inner conductive layer.

[0142] From the viewpoint of making the conductive part melt well and from the viewpoint of more effectively exerting the effect of the present invention, the conductive part preferably has a layer containing copper or nickel and an alloy layer containing an alloy of tin and indium. From the viewpoint of making the conductive part melt well, the alloy layer containing an alloy of tin and indium is preferably arranged on the outer surface of the copper or nickel layer.

[0143] From the viewpoint of further improving conduction reliability, the nickel content in 100 wt % of the nickel layer is preferably 10 wt % or more, more preferably 30 wt % or more, further preferably 44 wt % or more, preferably 90 wt % or less, more preferably 80 wt % or less, further preferably 72 wt % or less.

[0144] The content of the nickel (and other metals) in the nickel layer can be measured using a high-frequency inductively coupled plasma emission spectrometer or a fluorescent X-ray analyzer. Examples of the high-frequency inductively coupled plasma emission spectrometer include "ICP-AES" manufactured by Horiba, Ltd., and the like. Examples of the fluorescent X-ray analyzer include "EDX-800HS" manufactured by Shimadzu Corporation, and the like.

[0145] From the viewpoint of more effectively exerting the effects of the present invention, the melting point of the entire conductive portion in the conductive particles is preferably 200° C. or lower, more preferably 160° C. or lower, further preferably 155° C. or lower, particularly preferably 150° C. or lower, and most preferably 140° C. or lower. The melting point of the entire conductive portion in the conductive particles may be 25° C. or higher, or 50° C. or higher.

[0146] The melting point of the entire conductive portion can be measured by the following method.

[0147] 35 mg of the particles were measured using a differential scanning calorimeter (DSC) at a temperature increase rate of 5° C. / min. When there were multiple peaks, the peak with the lowest melting point was taken as the peak of the entire conductive portion.

[0148] From the viewpoint of sufficiently lowering the melting temperature of the conductive portion, when measuring the X-ray diffraction spectrum of the conductive portion, it is preferred that a peak exists in a region of 32° to 34° or less. From the viewpoint of sufficiently lowering the melting temperature of the conductive portion, when measuring the X-ray diffraction spectrum of the conductive portion, it is preferred that a peak exists in a region of 55.5° to 57.5° or less. From the viewpoint of sufficiently lowering the melting temperature of the conductive portion, when measuring the X-ray diffraction spectrum of the conductive portion, it is preferred that a peak exists in a region of 32° to 34° or less and in a region of 55.5° to 57.5° or less.

[0149] In the X-ray diffraction spectrum of the conductive portion, when there are peaks in the region of 32° to 34° and in the region of 55.5° to 57.5°, the highest peak height in the region of 32° to 34° is preferably higher than the highest peak height in the region of 55.5° to 57.5°. In this case, the content of the alloy with a low melting point in the conductive portion can be within a good range, and the melting temperature of the conductive portion can be sufficiently reduced.

[0150] The X-ray diffraction spectrum of the conductive portion can be measured using an X-ray diffraction device (for example, "RINT2500VHF" manufactured by Rigaku Corporation).

[0151] From the viewpoint of preventing oxidation of the metal of the conductive portion and removing an oxide film and foreign matter on the surface of the conductive portion to further improve conduction reliability, the outer surface of the conductive portion is preferably surface-treated with a flux. The flux is not particularly limited.

[0152] Examples of the soldering flux include zinc chloride, a mixture of zinc chloride and an inorganic halide, a mixture of zinc chloride and an inorganic acid, molten salts, phosphoric acid, a derivative of phosphoric acid, an organic halide, hydrazine, an amine compound, an organic acid, and rosin. The soldering flux may be used alone or in combination of two or more.

[0153] As the molten salt, ammonium chloride and the like can be cited. As the organic acid, lactic acid, citric acid, stearic acid, glutamic acid and glutaric acid and the like can be cited. As the rosin, activated rosin and non-activated rosin and the like can be cited. The soldering flux is preferably an organic acid or rosin having two or more carboxyl groups. The soldering flux can be an organic acid or rosin having two or more carboxyl groups. By using an organic acid or rosin having two or more carboxyl groups, the connection strength and conduction reliability are further improved.

[0154] Examples of the organic acid having two or more carboxyl groups include succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, and sebacic acid.

[0155] Examples of the amine compound include cyclohexylamine, dicyclohexylamine, benzylamine, dibenzhydrylamine, imidazole, benzimidazole, phenylimidazole, carboxybenzimidazole, benzotriazole, and carboxybenzotriazole.

[0156] The rosin is a rosin with abietic acid as the main component. Examples of the rosin include abietic acid and acrylic modified rosin. The soldering flux is preferably a rosin, more preferably abietic acid. By using the preferred soldering flux, the soldering flux effect is further improved.

[0157] The active temperature (melting point) of the soldering flux is preferably 50° C. or higher, more preferably 70° C. or higher, further preferably 80° C. or higher, preferably 200° C. or lower, more preferably 190° C. or lower, further preferably 160° C. or lower, further preferably 150° C. or lower, further preferably 140° C. or lower. When the active temperature of the soldering flux is above the lower limit and below the upper limit, the effect of the soldering flux is further improved.

[0158] The melting point of the flux can be determined by differential scanning calorimetry (DSC). Examples of the differential scanning calorimetry (DSC) apparatus include "EXSTAR DSC7020" manufactured by SII Corporation.

[0159] In addition, the boiling point of the soldering flux is preferably 200° C. or lower. The lower limit of the boiling point of the soldering flux is not particularly limited. The boiling point of the soldering flux may be 10° C. or higher, or 30° C. or higher.

[0160] The soldering flux is preferably a soldering flux that releases cations when heated. By using a soldering flux that releases cations when heated, the connection strength and conduction reliability are further improved.

[0161] Examples of the flux that releases cations when heated include the thermal cation initiator (thermal cation curing agent).

[0162] From the viewpoint of further enhancing the flux effect, the flux is preferably a salt of an acid compound and a base compound.

[0163] The acid compound is preferably an organic compound having a carboxyl group. Examples of the acid compound include malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, citric acid, malic acid, cyclohexylcarboxylic acid, 1,4-cyclohexyldicarboxylic acid, and aromatic carboxylic acids such as isophthalic acid, terephthalic acid, trimellitic acid, and ethylenediaminetetraacetic acid. From the perspective of further effectively improving the connection strength and the perspective of further effectively improving the conduction reliability, the acid compound is preferably glutaric acid, cyclohexylcarboxylic acid, or adipic acid.

[0164] The base compound is preferably an organic compound having an amino group. Examples of the base compound include diethanolamine, triethanolamine, methyldiethanolamine, ethyldiethanolamine, cyclohexylamine, dicyclohexylamine, benzylamine, dibenzylamine, 2-methylbenzylamine, 3-methylbenzylamine, 4-tert-butylbenzylamine, N-methylbenzylamine, N-ethylbenzylamine, N-phenylbenzylamine, N-tert-butylbenzylamine, N-isopropylbenzylamine, N,N-dimethylbenzylamine, imidazole compounds, and triazole compounds. From the viewpoint of further effectively improving the connection strength and the viewpoint of further effectively improving the conduction reliability, the base compound is preferably benzylamine.

[0165] In the total surface area 100% of the substrate particles, the area of ​​the conductive portion (based on the coverage of the conductive portion) is preferably 80% or more, more preferably 90% or more. The upper limit of the coverage based on the conductive portion is not particularly limited. The coverage based on the conductive portion can be 100%, or less than 100%, or less than 99%. When the coverage based on the conductive portion is above the lower limit, when the electrodes are electrically connected, the conduction reliability can be further effectively improved.

[0166] The thickness of the conductive portion is preferably 0.005 μm or more, more preferably 0.01 μm or more, further preferably 0.05 μm or more, preferably 10 μm or less, more preferably 1 μm or less, and further preferably 0.5 μm or less. When the thickness of the conductive portion is above the lower limit and below the upper limit, the conduction reliability can be further effectively improved, and the conductive particles will not become too hard, and the conductive particles can be fully deformed when connecting between electrodes. It should be noted that the thickness of the conductive portion is the average thickness of each of the conductive particles.

[0167] When the conductive portion is formed by a plurality of layers, the thickness of the outermost layer of the conductive portion is preferably 0.001 μm or more, more preferably 0.01 μm or more, preferably 0.5 μm or less, and more preferably 0.3 μm or less. When the thickness of the outermost layer of the conductive portion is above the lower limit and below the upper limit, the outermost layer of the conductive portion becomes uniform, the corrosion resistance becomes sufficiently high, and the connection resistance between the electrodes can be sufficiently reduced. It should be noted that the thickness of the outermost layer of the conductive portion is the average thickness of each of the conductive particles.

[0168] The thickness of the conductive portion and the thickness of the outermost layer of the conductive portion can be measured by observing a cross section of the conductive particle using a transmission electron microscope (TEM), for example.

[0169] The method for forming the conductive portion on the surface of the substrate particles is not particularly limited. As the method for forming the conductive portion, for example, there can be mentioned: a method utilizing chemical plating, a method utilizing electroplating, a method utilizing physical collision, a method utilizing a mechanochemical reaction, a method utilizing physical evaporation or physical adsorption, and a method of applying a paste comprising metal powder or metal powder and an adhesive to the surface of substrate particles, etc. The method for forming the conductive portion is preferably a method utilizing chemical plating, electroplating or physical collision. As the method utilizing physical evaporation, methods such as vacuum evaporation, ion plating and ion sputtering can be cited. In addition, in the method utilizing physical collision, for example, THETA COMPOSER (manufactured by Deju Works) is used.

[0170] <Insulating Particles>

[0171] The conductive particles of the present invention preferably have a plurality of insulating particles on the surface of the conductive particles. In this case, if the conductive particles are used for connection between electrodes, short circuits between adjacent electrodes can be prevented. Specifically, when a plurality of conductive particles are in contact with each other, insulating particles are present between a plurality of electrodes, so that short circuits between electrodes adjacent to each other in the horizontal direction can be prevented instead of between upper and lower electrodes. It should be noted that, when connecting between electrodes, by pressurizing the conductive particles with two electrodes, the insulating particles between the conductive particles and the electrodes can be easily excluded. In addition, in the case of conductive particles having a plurality of projections on the outer surface of the conductive portion, the insulating particles between the conductive particles and the electrodes can be more easily excluded.

[0172] The insulating particles are preferably polymers of polymerizable compounds. The polymerizable compounds are not particularly limited. Examples of the polymerizable compounds include materials of the resin particles. From the perspective of improving the adhesion between the conductive particles and the insulating particles and further improving the insulation reliability, the insulating particles are preferably resin particles.

[0173] As a method for configuring the insulating particles on the surface of the conductive portion, there are chemical methods, physical or mechanical methods, etc. As the chemical method, for example, there are interfacial polymerization, suspension polymerization in the presence of particles, and emulsion polymerization. As the physical or mechanical method, there are spray drying, hybridization, electrostatic adhesion, spraying, methods based on immersion and vacuum evaporation, etc. In the case of electrically connecting the electrodes, from the viewpoint of further effectively improving the insulation reliability and conduction reliability, the method of configuring the insulating particles on the surface of the conductive portion is preferably a physical method.

[0174] The particle size of the insulating particles can be appropriately selected according to the particle size of the conductive particles and the purpose of the conductive particles. The particle size of the insulating particles is preferably 10 nm or more, more preferably 100 nm or more, further preferably 200 nm or more, particularly preferably 300 nm or more, preferably 4000 nm or less, more preferably 2000 nm or less, further preferably 1500 nm or less, and particularly preferably 1000 nm or less. If the particle size of the insulating particles is above the lower limit, when the conductive particles are dispersed in the binder resin, a plurality of the conductive particles are not easily in contact with each other. If the particle size of the insulating particles is below the upper limit, when connecting between electrodes, there is no need to excessively increase the pressure in order to exclude the insulating particles between the electrode and the conductive particles, and there is no need to heat to a high temperature.

[0175] The particle size of the insulating particles is preferably an average particle size, which represents a number average particle size. The particle size of the insulating particles is obtained using a particle size distribution measuring device or the like. The particle size of the insulating particles is preferably obtained by observing 50 arbitrary insulating particles with an electron microscope or an optical microscope and calculating the average value; or by performing a laser diffraction particle size distribution measurement. In the conductive particles, when the particle size of the insulating particles is measured, it can be measured, for example, as follows.

[0176] The conductive particles are added to "TECHNOVIT4000" manufactured by Kulzer Company in a manner such that the content is 30% by weight, and the particles are dispersed to prepare an embedded resin for inspection containing conductive particles. The cross-section of the conductive particles is cut out using an ion milling device ("IM4000" manufactured by Hitachi High-Technologies Corporation) in a manner near the center of the dispersed conductive particles in the embedded resin for inspection. Then, using a field emission scanning electron microscope (FE-SEM), the image magnification is set to 50,000 times, 50 conductive particles are randomly selected, and the insulating particles of each conductive particle are observed. The equivalent circle diameter of the insulating particles in each conductive particle is measured as the particle size, and they are arithmetic averaged as the particle size of the insulating particles.

[0177] The conductive particles of the present invention may be used in combination of two or more insulating particles having different particle sizes. By using two or more insulating particles having different particle sizes in combination, the insulating particles having a smaller particle size enter the gaps covered by the insulating particles having a larger particle size, and the insulating particles can be more efficiently arranged on the surface of the conductive particles.

[0178] The coefficient of variation (CV value) of the particle size of the insulating particles is preferably 20% or less. If the coefficient of variation of the particle size of the insulating particles is below the upper limit, the thickness of the insulating particles in the obtained conductive particles becomes more uniform, and pressure can be more easily and uniformly applied during conductive connection, which can further reduce the connection resistance between electrodes.

[0179] The coefficient of variation (CV value) can be determined as follows.

[0180] CV value (%) = (ρ / Dn) × 100

[0181] ρ: Standard deviation of particle size of insulating particles

[0182] Dn: average value of the particle size of insulating particles

[0183] The shape of the insulating particles is not particularly limited. The insulating particles may be spherical, may be other than spherical, and may be flat.

[0184] From the viewpoint of improving insulation reliability, the area of ​​the portion covered by the insulating particles (based on the coverage rate of the insulating particles) in the total surface area of ​​100% of the conductive portion is preferably 30% or more, more preferably 35% or more, and preferably 70% or less, more preferably 60% or less.

[0185] The coverage rate based on the insulating particles can be measured, for example, by the following method. Using a field emission scanning electron microscope (FE-SEM), the image magnification is set to 50,000 times, 20 conductive particles are randomly selected, and the surface of each conductive particle is observed. In the obtained conductive particles, the percentage of the surface area of ​​the portion covered by the insulating particles relative to the projected area of ​​the entire particle is measured, and the arithmetic average is taken as the coverage rate based on the insulating particles.

[0186] Furthermore, the coverage rate by the insulating particles can also be measured by mapping analysis such as EDX attached to SEM.

[0187] The method for adjusting the coverage by the insulating particles is not particularly limited. The coverage by the insulating particles can be adjusted, for example, by the amount of inorganic particles added to the base particles and the mixing time.

[0188] (Conductive materials)

[0189] The conductive material of the present invention comprises the conductive particles and a binder resin. The conductive particles are preferably dispersed in a binder resin for use. The conductive particles are preferably dispersed in a binder resin for use as a conductive material. The conductive material is preferably an anisotropic conductive material. The conductive material is preferably used for electrical connection between electrodes. The conductive material is preferably a conductive material for circuit connection.

[0190] The binder resin is not particularly limited. As the binder resin, a known insulating resin can be used. The binder resin preferably contains a thermoplastic component (thermoplastic compound) or a curable component, and more preferably contains a curable component. As the curable component, a photocurable component and a thermosetting component can be mentioned. The photocurable component preferably contains a photocurable compound and a photopolymerization initiator. The thermosetting component preferably contains a thermosetting compound and a thermosetting agent.

[0191] Examples of the binder resin include vinyl resins, thermoplastic resins, curable resins, thermoplastic block copolymers, and elastomers. The binder resin may be used alone or in combination of two or more.

[0192] As the vinyl resin, for example, vinyl acetate resin, acrylic resin and styrene resin can be cited. As the thermoplastic resin, for example, polyolefin resin, ethylene-vinyl acetate copolymer and polyamide resin can be cited. As the curable resin, for example, epoxy resin, polyurethane resin, polyimide resin and unsaturated polyester resin can be cited. It should be noted that the curable resin can also be a room temperature curing resin, a heat curing resin, a light curing resin or a moisture curing resin. The curable resin can be used in combination with a curing agent. Examples of the thermoplastic block copolymer include styrene-butadiene-styrene block copolymer, styrene-isoprene-styrene block copolymer, a hydrogenated product of styrene-butadiene-styrene block copolymer and a hydrogenated product of styrene-isoprene-styrene block copolymer. Examples of elastomers include styrene-butadiene copolymer rubber and acrylonitrile-styrene block copolymer rubber.

[0193] The conductive material may contain various additives such as fillers, extenders, softeners, plasticizers, polymerization catalysts, curing catalysts, colorants, antioxidants, heat stabilizers, light stabilizers, ultraviolet absorbers, lubricants, antistatic agents, and flame retardants in addition to the conductive particles and the binder resin.

[0194] The method for dispersing the conductive particles in the binder resin may be a conventionally known dispersion method, and is not particularly limited. As the method for dispersing the conductive particles in the binder resin, for example, the following methods can be cited. A method in which the conductive particles are added to the binder resin and then dispersed by kneading with a planetary mixer or the like. A method in which the conductive particles are uniformly dispersed in water or an organic solvent using a homogenizer or the like, and then added to the binder resin and dispersed by kneading with a planetary mixer or the like. A method in which the binder resin is diluted with water or an organic solvent or the like, and then the conductive particles are added and dispersed by kneading with a planetary mixer or the like.

[0195] The viscosity (η25) of the conductive material at 25°C is preferably 30 Pa·s or more, more preferably 50 Pa·s or more, preferably 400 Pa·s or less, and more preferably 300 Pa·s or less. When the viscosity of the conductive material at 25°C is above the lower limit and below the upper limit, the insulation reliability between the electrodes can be further effectively improved, and the conduction reliability between the electrodes can be further effectively improved. The viscosity (η25) can be appropriately adjusted according to the type and amount of the compounding component.

[0196] The viscosity (η25) can be measured under the conditions of 25° C. and 5 rpm using, for example, an E-type viscometer (“TVE22L” manufactured by Toki Sangyo Co., Ltd.).

[0197] The conductive material can be used as a conductive paste, a conductive film, etc. When the conductive material is a conductive film, a film not containing conductive particles can be laminated on the conductive film containing conductive particles. The conductive paste is preferably an anisotropic conductive paste. The conductive film is preferably an anisotropic conductive film.

[0198] In 100 wt % of the conductive material, the content of the binder resin is preferably 10 wt % or more, more preferably 30 wt % or more, further preferably 50 wt % or more, particularly preferably 70 wt % or more, preferably 99.99 wt % or less, more preferably 99.9 wt % or less. If the content of the binder resin is above the lower limit and below the upper limit, conductive particles can be efficiently arranged between electrodes, further improving the connection reliability of the connection object parts connected by the conductive material.

[0199] In 100 wt % of the conductive material, the content of the conductive particles is preferably 0.01 wt % or more, more preferably 0.1 wt % or more, preferably 80 wt % or less, more preferably 60 wt % or less, further preferably 40 wt % or less, particularly preferably 20 wt % or less, and most preferably 10 wt % or less. When the content of the conductive particles is above the lower limit and below the upper limit, the conduction reliability and the insulation reliability can be further improved.

[0200] (Connection structure)

[0201] The connection structure of the present invention comprises: a first connection object part having a first electrode on its surface; a second connection object part having a second electrode on its surface; and a connection portion connecting the first connection object part and the second connection object part. In the connection structure of the present invention, the material of the connection portion includes the conductive particles. In the connection structure of the present invention, the first electrode and the second electrode are electrically connected via the conductive particles.

[0202] Figure 5 This is a cross-sectional view schematically showing a connection structure using conductive particles according to the first embodiment of the present invention.

[0203] Figure 5 The connection structure 51 shown includes a first connection object part 52, a second connection object part 53, and a connection part 54 connecting the first connection object part 52 and the second connection object part 53. The material of the connection part 54 includes conductive particles 1. The connection part 54 can also be formed by a conductive material including conductive particles 1. The connection part 54 is preferably formed by curing a conductive material including a plurality of conductive particles 1. Figure 4In the figure, for convenience of illustration, the conductive particle 1 is schematically shown. In place of the conductive particle 1, the conductive particle 11, the conductive particle 21, or the conductive particle 31 may be used.

[0204] The first connection object member 52 has a plurality of first electrodes 52a on the surface (upper surface). The second connection object member 53 has a plurality of second electrodes 53a on the surface (lower surface). The first electrode 52a and the second electrode 53a are electrically connected via one or more conductive particles 1. Therefore, the first connection object member 52 and the second connection object member 53 are electrically connected via the conductive portion 3 in the conductive particle 1.

[0205] The method for manufacturing the connection structure is not particularly limited. As an example of a method for manufacturing a connection structure, there can be cited a method in which the conductive material is arranged between the first connection object part and the second connection object part, and after obtaining a laminate, the laminate is heated and pressurized. The pressure of the thermocompression bonding is preferably 40 MPa or more, more preferably 60 MPa or more, preferably 90 MPa or less, and more preferably 70 MPa or less. The heating temperature of the thermocompression bonding is preferably 80°C or more, more preferably 100°C or more, preferably 140°C or less, and more preferably 120°C or less. When the pressure and temperature of the thermocompression bonding are above the lower limit and below the upper limit, the insulating particles can be easily detached from the surface of the conductive particles during the conductive connection, and the conduction reliability between the electrodes can be further improved.

[0206] When the laminate is heated and pressurized, the insulating particles present between the conductive particles and the first electrode and the second electrode can be removed. For example, during the heating and pressurization, the insulating particles present between the conductive particles and the first electrode and the second electrode are easily detached from the surface of the conductive particles with insulating particles. It should be noted that during the heating and pressurization, sometimes a part of the insulating particles detach from the surface of the conductive particles with insulating particles, and the surface of the conductive part is partially exposed. The exposed part of the surface of the conductive part is in contact with the first electrode and the second electrode, and the first electrode and the second electrode can be electrically connected via the conductive particles.

[0207] The first connection object component and the second connection object component are not particularly limited. Specifically, the first connection object component and the second connection object component include electronic components such as semiconductor chips, semiconductor packages, LED chips, LED packages, capacitors, and diodes, and electronic components such as circuit substrates such as resin films, printed substrates, flexible printed substrates, flexible flat cables, rigid-flexible substrates, glass epoxy substrates, and glass substrates. The first connection object component and the second connection object component are preferably electronic components.

[0208] As the electrode provided on the connection object part, metal electrodes such as gold electrode, nickel electrode, tin electrode, aluminum electrode, copper electrode, molybdenum electrode, silver electrode, SUS electrode and tungsten electrode can be cited. When the connection object part is a flexible printed substrate, the electrode is preferably a gold electrode, a nickel electrode, a tin electrode, a silver electrode or a copper electrode. When the connection object part is a glass substrate, the electrode is preferably an aluminum electrode, a copper electrode, a molybdenum electrode, a silver electrode or a tungsten electrode. It should be noted that when the electrode is an aluminum electrode, it can be an electrode formed only of aluminum, or it can be an electrode having an aluminum layer laminated on the surface of a metal oxide layer. As the material of the metal oxide layer, indium oxide doped with a trivalent metal element and zinc oxide doped with a trivalent metal element can be cited. As the trivalent metal element, Sn, Al and Ga can be cited.

[0209] The present invention will be described in detail below with reference to Examples and Comparative Examples, but the present invention is not limited to the following Examples.

[0210] (Example 1)

[0211] (1) Preparation of conductive particles

[0212] Formation of the first conductive portion:

[0213] As substrate particles A, acrylic copolymer resin particles ("MICROPEARL EZ3P-020" manufactured by Sekisui Chemical Co., Ltd., average particle size 20 μm) were prepared. In 100 parts by weight of an alkaline solution containing 5% by weight of a palladium catalyst solution, 10 parts by weight of the substrate particles A were dispersed using an ultrasonic disperser, and the solution was filtered to remove the substrate particles A. Next, the substrate particles A were added to 100 parts by weight of a 1% by weight solution of dimethylamine borane to activate the surface of the substrate particles A. The surface-activated substrate particles A were fully washed with water, added to 500 parts by weight of distilled water, and dispersed to obtain a dispersion A containing the substrate particles A. 1 g of nickel particle slurry (average particle size 100 nm) was added to the dispersion A for 3 minutes to obtain a suspension A containing the substrate particles A with a core material attached.

[0214] Furthermore, as a nickel plating solution, a nickel plating solution (pH 8.5) containing 0.14 mol / L of nickel sulfate, 0.46 mol / L of dimethylamine borane, and 0.2 mol / L of sodium citrate was prepared.

[0215] While stirring the obtained suspension A at 70° C., the nickel plating solution was added dropwise to the suspension A at a dropping speed of 30 mL / min for 10 minutes. Then, the nickel plating solution was added dropwise at a dropping speed of 10 mL / min for 40 minutes, and then at a dropping speed of 4 mL / min for 80 minutes, thereby performing chemical nickel-boron alloy plating while controlling the content of boron entering the plated film.

[0216] Then, the suspension A was filtered to take out particles, washed with water, and dried to obtain particles A having the first conductive portion (nickel layer, 250 nm thick) arranged on the surface of the substrate particles A.

[0217] Formation of the second conductive portion:

[0218] 10 parts by weight of the obtained particles A were dispersed in 500 parts by weight of ion-exchanged water using an ultrasonic processor, whereby a suspension B was obtained.

[0219] A tin plating solution containing 15 g / L tin sulfate, 45 g / L ethylenediaminetetraacetic acid, 30 g / L sodium gluconate, and 1.5 g / L phosphinic acid (adjusted to pH 8.5 with sodium hydroxide) was prepared. In addition, a reducing solution containing 5 g / L sodium borohydride (adjusted to pH 10.0 with sodium hydroxide) was prepared.

[0220] The suspension B obtained was stirred at 55°C while the tin plating solution was slowly added, and then reduced with a reducing solution to perform chemical tin plating to form a second conductive portion. The chemical tin plating was terminated when the thickness of the second conductive portion reached 125 nm. Particles B having a second conductive portion (tin layer, thickness 125 nm) arranged on the surface of the first conductive portion were obtained.

[0221] Formation of the third conductive portion:

[0222] 10 parts by weight of the obtained particles B were dispersed in 500 parts by weight of ion-exchanged water using an ultrasonic processor, thereby obtaining a suspension C.

[0223] An indium plating solution containing a crystal modifier (adjusted to pH 10.0 with sodium hydroxide) was prepared, wherein the crystal modifier contained 0.02 mol / L indium sulfate, 0.04 mol / L ethylenediamine as a complexing agent, and 0.04 mol / L sodium gluconate. In addition, a reducing solution containing 5 g / L sodium borohydride (adjusted to pH 10.0 with sodium hydroxide) was prepared.

[0224] The suspension C obtained was stirred at 60°C while the indium plating solution was slowly added, and then reduced with a reducing solution to perform chemical indium plating to form a third conductive portion. The chemical indium plating was terminated when the thickness of the third conductive portion reached 125 nm. Conductive particles (before flux treatment) having the third conductive portion (indium layer, thickness 125 nm) arranged on the surface of the second conductive portion were obtained.

[0225] Flux treatment:

[0226] The obtained conductive particles were dispersed in 200 mL of ethanol to obtain a dispersion. The dispersion was then mixed with 300 mL of ethanol in which 0.5 g of flux was dissolved, and stirred for 10 minutes at a temperature of 50°C under ultrasonic dispersion. The mixture was filtered through a 3 μm mesh filter and dried. In this way, conductive particles whose outer surfaces of the conductive parts were surface-treated with flux were obtained.

[0227] (2) Preparation of conductive materials

[0228] Mix the following materials to obtain a mixture. 10 parts by weight of bisphenol A epoxy resin ("EPIKOTE1009" manufactured by Mitsubishi Chemical Corporation). 40 parts by weight of acrylic rubber (weight average molecular weight of about 800,000). 200 parts by weight of methyl ethyl ketone. 50 parts by weight of microcapsule curing agent ("HX3941HP" manufactured by Asahi Kasei Electronic Materials Co., Ltd.). 2 parts by weight of silane coupling agent ("SH6040" manufactured by Toray Dow Corning Polysiloxane Co., Ltd.). Add conductive particles to the mixture in an amount of 3% by weight and disperse them to obtain a conductive material.

[0229] The obtained conductive material was applied to a 50 μm thick PET (polyethylene terephthalate) film with a mold release treatment on one side, and dried with hot air at 70° C. for 5 minutes to prepare an anisotropic conductive film. The obtained anisotropic conductive film had a thickness of 50 μm.

[0230] (3) Preparation of the connection structure

[0231] A polyimide substrate (flexible printed substrate) having an Au electrode pattern (electrode (Au circuit): Ni / Au thin film on Cu) with an L / S of 200 μm / 200 μm on the upper surface was prepared. In addition, a printed substrate having an Au electrode pattern (electrode (Au bump): Ni / Au thin film on Cu) with an L / S of 200 μm / 200 μm on the lower surface was prepared. The upper surface of the polyimide substrate was heated at 80°C and 0.98 MPa (10 kgf / cm 2) After attaching the obtained anisotropic conductive film, the diaphragm is peeled off. Then, the Au bumps of the printed substrate and the Au circuits of the polyimide substrate are aligned. Next, a pressurized heating head is placed on the upper surface of the semiconductor chip, and a low pressure of 1 MPa calculated from the crimping area is applied while the anisotropic conductive material layer is cured at 1) 135°C, 2) 160°C or 3) the melting point of the conductive part in each conductive particle + 20°C to obtain a connected structure.

[0232] (Example 5)

[0233] Formation of the second conductive portion:

[0234] Particles A having a first conductive portion (nickel layer, 250 nm thick) disposed on the surface of substrate particles A were prepared in the same manner as in Example 1. 10 parts by weight of particles A were thoroughly washed with water and then dispersed in 500 parts by weight of distilled water using an ultrasonic processor to obtain a suspension (B5).

[0235] 2 L of a gold plating solution (pH 9.0) containing 0.011 mol / L potassium gold cyanide, 0.20 mol / L sodium citrate, 0.08 mol / L ethylenediaminetetraacetic acid, and 0.5 mol / L sodium hydroxide was prepared. Also, 1.5 L of a reducing solution (pH 9.0) containing 0.09 mol / L dimethylamine borane and 0.10 mol / L sodium hydroxide was prepared.

[0236] While stirring the obtained suspension (B5) at 55° C., 0.5 L of the gold plating solution was slowly added dropwise to perform displacement gold plating. Next, 1.5 L of the gold plating solution and 1.5 L of the reducing solution were simultaneously slowly added dropwise to the suspension (B5) to perform reduction gold plating.

[0237] Then, the suspension (B5) was filtered, the particles were taken out, washed with water, and dried, thereby obtaining particles (B5) in which the second conductive part (gold layer, thickness 20 nm) was arranged on the surface of the first conductive part.

[0238] Formation of the third and fourth conductive parts:

[0239] Then, 10 parts by weight of the obtained particles (B5) were fully washed with water, and then dispersed in 500 parts by weight of ion exchange water using an ultrasonic processor to obtain a suspension (C5). Except for using the obtained suspension (C5), the same operation as the method for forming the second conductive portion and the method for forming the third conductive portion of Example 1 was performed to obtain conductive particles (before flux treatment) having a third conductive portion (tin layer, thickness 125 nm) and a fourth conductive portion (indium layer, thickness 125 nm) arranged on the surface of the second conductive portion. For the obtained conductive particles (before flux treatment), flux treatment was performed in the same manner as in Example 1 to obtain conductive particles, conductive materials and connection structures.

[0240] (Example 6)

[0241] Formation of the first conductive portion:

[0242] Prepare a copper plating solution (adjusted to pH 10.5 with ammonia) containing 200 g / L of copper sulfate, 150 g / L of ethylenediaminetetraacetic acid, 100 g / L of sodium gluconate and 50 g / L of formaldehyde. Use the copper plating solution to replace the nickel plating solution in the formation of the first conductive part of Example 1, while stirring the suspension A at 65 ° C, while adding 250 ml of copper plating solution to the suspension A at 10 ml / min, and chemical copper plating is performed. Thereafter, stirring until the pH is stable, after confirming that the bubbling of hydrogen has stopped, the particles are taken out by filtering, washed with water, and dried to form the first conductive part (copper layer, thickness 250 nm) on the surface of the substrate particles A.

[0243] Formation of the second and third conductive parts:

[0244] Except having used the copper layer as the first conductive part, the second conductive part and the third conductive part were formed in the same manner as in Example 1, thereby obtaining conductive particles, a conductive material, and a connection structure.

[0245] (Example 7)

[0246] Formation of the second conductive portion:

[0247] In the same manner as in Example 1, a suspension B in which particles A having a first conductive portion (nickel layer, 250 nm in thickness) dispersed therein was prepared. In addition, a tin-indium plating solution (1) containing 15 g / L of tin sulfate, 34 g / L of indium sulfate, 70 g / L of ethylenediaminetetraacetic acid, 30 g / L of sodium gluconate, and 1.5 g / L of phosphinic acid was prepared (pH adjusted to 8.5 using sodium hydroxide). In addition, a reducing solution containing 5 g / L of sodium borohydride was prepared (pH adjusted to 10.0 using sodium hydroxide).

[0248] After slowly adding the tin-indium plating solution (1) while stirring the suspension B at 55°C, the suspension was reduced with the reducing solution to perform chemical tin-indium plating to form a second conductive portion. Conductive particles (before flux treatment) were obtained in which the second conductive portion (tin-indium layer, thickness 250nm) was arranged on the surface of the first conductive portion (nickel layer, thickness 250nm). The obtained conductive particles (before flux treatment) were subjected to flux treatment in the same manner as in Example 1 to obtain conductive particles, conductive materials, and connection structures.

[0249] (Example 11)

[0250] Formation of the first conductive portion:

[0251] In the same manner as in Example 6, a first conductive portion (copper layer, 250 nm in thickness) was formed on the surface of the substrate particle A.

[0252] Formation of the second conductive portion:

[0253] Then, the same operation as the method for forming the second conductive portion in Example 7 was performed to obtain conductive particles (before flux treatment) in which the second conductive portion (tin-indium layer, thickness 250 nm) was arranged on the surface of the first conductive portion. The obtained conductive particles (before flux treatment) were subjected to flux treatment in the same manner as in Example 1 to obtain conductive particles, a conductive material, and a connection structure.

[0254] (Comparative Example 1)

[0255] The same operation as in Example 1 was performed to obtain conductive particles (before flux treatment) in which a first conductive portion (nickel layer, thickness 250 nm) and a second conductive portion (tin layer, thickness 250 nm) were arranged on the surface of the substrate particle A. The obtained conductive particles (before flux treatment) were subjected to flux treatment in the same manner as in Example 1 to obtain conductive particles, a conductive material, and a connection structure.

[0256] (Comparative Example 3)

[0257] The same operation as in Example 1 was performed to obtain particles having a first conductive portion (nickel layer, thickness 1000nm) configured on the surface of substrate particles A. Then, using THETA COMPOSER (manufactured by Tokushou Works), on the surface of the first conductive portion, solder powder (containing 90% by weight of tin and 10% by weight of bismuth, with an average particle size of 200nm) was melted to form a second conductive portion (tin-bismuth layer, thickness 1000nm) on the surface of the first conductive portion. Next, using THETA COMPOSER (manufactured by Tokushou Works), solder powder (containing 42% by weight of tin and 58% by weight of bismuth, with an average particle size of 200nm) was melted on the surface of the obtained second conductive portion to obtain conductive particles having a third conductive portion (tin-bismuth layer, thickness 1000nm) configured on the surface of the second conductive portion. In addition to using the obtained conductive particles, a conductive material and a connection structure were obtained in the same manner as in Example 1.

[0258] (Comparative Example 4)

[0259] The same operation as in Example 6 was performed to obtain particles having a first conductive portion (copper layer, thickness 1000nm) configured on the surface of substrate particles A. Then, in the same manner as the formation method of the second conductive portion of Comparative Example 3, a second conductive portion (tin-bismuth layer, formed using solder powder containing 90% by weight of tin and 10% by weight of bismuth, thickness 1000nm) was formed on the surface of the first conductive portion. Next, the same operation as the formation method of the third conductive portion of Comparative Example 3 was performed to obtain conductive particles having a third conductive portion (tin-bismuth layer, formed using solder powder containing 42% by weight of tin and 58% by weight of bismuth, thickness 1000nm) configured on the surface of the second conductive portion. In addition to using the obtained conductive particles, a conductive material and a connection structure were obtained in the same manner as in Example 1.

[0260] (Comparative Example 6)

[0261] Formation of the first and second conductive parts:

[0262] The same operation as in Example 1 was performed to obtain particles (X6) having a first conductive portion (nickel layer, thickness 250 nm) and a second conductive portion (tin layer, thickness 118 nm) disposed on the surface of the substrate particle A. Then, 10 parts by weight of the obtained particles (X6) were dispersed in 500 parts by weight of ion exchange water using an ultrasonic processor to obtain a suspension (X6).

[0263] A bismuth plating solution containing a crystal modifier (adjusted to pH 10.0 with sodium hydroxide) was prepared, wherein the crystal modifier contained 0.013 mol / L of bismuth sulfate and 0.04 mol / L of ethylenediamine as a complexing agent. In addition, a reducing solution containing 5 g / L of sodium borohydride (adjusted to pH 10.0 with sodium hydroxide) was prepared.

[0264] While stirring the obtained suspension (X6) at 60°C, the bismuth plating solution is slowly added, and then reduced with a reducing solution to perform chemical bismuth plating to form a third conductive portion. The chemical bismuth plating is terminated when the thickness of the third conductive portion reaches 130nm. Conductive particles (before flux treatment) having a third conductive portion (bismuth layer, thickness 130nm) arranged on the surface of the second conductive portion are obtained. For the obtained conductive particles (before flux treatment), flux treatment is performed in the same manner as in Example 1 to obtain conductive particles, conductive materials and connection structures.

[0265] (Comparative Example 10)

[0266] The same operation as in Example 5 was performed to obtain particles having a first conductive portion (nickel layer, thickness 250nm) and a second conductive portion (gold layer, thickness 20nm) disposed on the surface of the substrate particle A. Then, the same operation as the method for forming the third conductive portion of Example 1 was performed to obtain conductive particles (before flux treatment) having a third conductive portion (indium layer, 125nm) disposed on the surface of the second conductive portion. The obtained conductive particles (before flux treatment) were subjected to flux treatment in the same manner as in Example 1 to obtain conductive particles, conductive materials, and connection structures.

[0267] (Comparative Example 11)

[0268] The same operation as in Example 5 was performed to obtain particles having a first conductive portion (nickel layer, thickness 250nm) and a second conductive portion (gold layer, thickness 20nm) configured on the surface of substrate particle A. Then, the same operation as the formation method of the second conductive portion and the formation method of the third conductive portion of Comparative Example 6 was performed to obtain conductive particles (before flux treatment) having a third conductive portion (tin layer, 118nm) and a fourth conductive portion (bismuth layer, thickness 130nm) configured on the surface of the second conductive portion. For the obtained conductive particles (before flux treatment), flux treatment was performed in the same manner as in Example 1 to obtain conductive particles, conductive materials and connection structures.

[0269] (Comparative Example 12)

[0270] The same operation as in Example 6 was performed to obtain particles having a first conductive portion (copper layer, thickness 250 nm) and a second conductive portion (tin layer, thickness 118 nm) disposed on the surface of the substrate particle A. Then, the same operation as the formation method of the third conductive portion of Comparative Example 6 was performed to obtain conductive particles (before flux treatment) having a third conductive portion (bismuth layer, thickness 130 nm). For the obtained conductive particles (before flux treatment), flux treatment was performed in the same manner as in Example 1 to obtain conductive particles, conductive materials, and connection structures.

[0271] (Comparative Example 13)

[0272] It carried out similarly to Example 6, and obtained the particle (X13) in which the 1st electroconductive part (copper layer, thickness 250nm) was formed on the surface of the substrate particle A.

[0273] Then, 10 parts by weight of the particles (X13) were thoroughly washed with water and then dispersed in 500 parts by weight of ion-exchanged water using an ultrasonic processor to obtain a suspension (X13).

[0274] As a nickel plating solution, a nickel plating solution (pH 8.5) containing 0.14 mol / L of nickel sulfate, 0.46 mol / L of dimethylamine borane, and 0.2 mol / L of sodium citrate was prepared.

[0275] The obtained suspension (X13) was stirred at 70° C., and the nickel plating solution was added dropwise at a dropping speed of 30 mL / min for 10 minutes. Then, the nickel plating solution was added dropwise at a dropping speed of 10 mL / min for 40 minutes, and then at a dropping speed of 4 mL / min for 80 minutes, thereby controlling the content of boron entering the plated film while performing chemical nickel-boron alloy plating.

[0276] Then, the suspension (X13) was filtered to take out particles, which were washed with water and dried to obtain particles having a second conductive portion (nickel layer, 250 nm in thickness) arranged on the surface of the first conductive portion.

[0277] Then, the same operation as the method for forming the third conductive portion in Example 1 was performed to obtain conductive particles (before flux treatment) in which the third conductive portion (indium layer, thickness 125 nm) was arranged on the surface of the second conductive portion. The obtained conductive particles (before flux treatment) were subjected to flux treatment in the same manner as in Example 1 to obtain conductive particles, a conductive material, and a connection structure.

[0278] (Comparative Example 14)

[0279] By electroplating the substrate particles A of Example 1, particles having a first conductive portion (zinc layer, 250 nm) disposed on the surface of the substrate particles A were obtained. Then, the same operation as the method for forming the second conductive portion and the method for forming the third conductive portion of Example 1 was performed to obtain conductive particles (before flux treatment) having a second conductive portion (tin layer, thickness 125 nm) and a third conductive portion (indium layer, thickness 125 nm) disposed on the surface of the first conductive portion. The obtained conductive particles (before flux treatment) were subjected to flux treatment in the same manner as in Example 1 to obtain conductive particles, conductive materials, and connection structures.

[0280] (Comparative Example 16)

[0281] In the same manner as in Example 1, a suspension B in which particles A having a first conductive portion (nickel layer, thickness 250 nm) dispersed therein was prepared. In addition, a tin-indium plating solution (1) containing 15 g / L of tin sulfate, 24 g / L of bismuth sulfate, 70 g / L of ethylenediaminetetraacetic acid, 30 g / L of sodium gluconate, and 1.5 g / L of phosphinic acid was prepared (pH adjusted to 8.5 using sodium hydroxide). In addition, a reducing solution containing 5 g / L of sodium borohydride was prepared (pH adjusted to 10.0 using sodium hydroxide).

[0282] While stirring the suspension B at 55°C, the tin-bismuth plating solution (1) was slowly added to the suspension B, and then reduced with the reducing solution to perform chemical tin-bismuth plating to form a second conductive portion. Conductive particles (before flux treatment) having a second conductive portion (tin-bismuth layer, thickness 248 nm) arranged on the surface of the first conductive portion were obtained. The obtained conductive particles (before flux treatment) were subjected to flux treatment in the same manner as in Example 1 to obtain conductive particles, a conductive material, and a connection structure.

[0283] (Comparative Example 17)

[0284] The same operation as in Example 6 was performed to obtain particles having a first conductive portion (copper layer, thickness 250nm) formed on the surface of substrate particles A. Then, chemical tin-bismuth plating was performed in the same manner as in Comparative Example 16 to form a second conductive portion. Conductive particles (before flux treatment) having a second conductive portion (tin-bismuth layer, thickness 248nm) arranged on the surface of the first conductive portion were obtained. For the obtained conductive particles (before flux treatment), flux treatment was performed in the same manner as in Example 1 to obtain conductive particles, conductive materials and connection structures.

[0285] (Examples 2-4, 8-10, 12-13 and Comparative Examples 2, 5, 7-9, 15)

[0286] With respect to Examples 2 to 4 and Comparative Examples 2 and 5, conductive particles, conductive materials, and connection structures were obtained in the same manner as in Example 1, except that the configuration of the conductive portion, the presence or absence of protrusions, and the presence or absence of flux treatment were changed as shown in Tables 1, 5, and 7 below. With respect to Examples 8 to 10, 12 to 13, and Comparative Example 15, conductive particles, conductive materials, and connection structures were obtained in the same manner as in Example 7, except that the configuration of the conductive portion, the presence or absence of protrusions, and the presence or absence of flux treatment were changed as shown in Tables 3, 5, and 11 below. With respect to Comparative Examples 7 to 9, conductive particles, conductive materials, and connection structures were obtained in the same manner as in Comparative Example 6, except that the configuration of the conductive portion, the presence or absence of protrusions, and the presence or absence of flux treatment were changed as shown in Tables 7 and 9 below. It should be noted that in the table, "the content in 100% by weight of the conductive part" represents the content (weight %) of the first, second, third and fourth conductive parts in 100% by weight of the conductive part (the total of the first, second, third and fourth conductive parts), and "the content in 100% by weight of the conductive particles" represents the content (weight %) of the first, second, third and fourth conductive parts in 100% by weight of the conductive particles.

[0287] (evaluate)

[0288] (1) Melting point of the entire conductive part

[0289] The melting point of the entire conductive portion in the obtained conductive particles is measured by the above method.

[0290] (2) X-ray diffraction spectrum

[0291] For the obtained conductive particles, an X-ray diffraction device ("RINT2500VHF" manufactured by Rigaku Electric Co., Ltd.) was used to measure the X-ray diffraction spectrum of the conductive portion, and the presence or absence of peaks in the region of 32° to 34° and in the region of 55.5° to 57.5° was observed. The measurement conditions of the X-ray diffraction spectrum were 45 kV, 50 mA, a scanning rate of 4.0 deg / min, a scanning step of 0.02 deg, and a measurement range of 5.0 deg to 110.0 deg in 2θ.

[0292] (3) Hot and cold cycle characteristics

[0293] The connection structure prepared under the condition of 2) 160°C was heated from -65°C to 150°C, and the process of cooling to -65°C was regarded as one cycle, and the hot and cold cycle test was carried out for 1000 cycles. The conductive particles were observed for cracks and peeling using an ultrasonic flaw detector (SAT). The hot and cold cycle characteristics were determined according to the following criteria based on the occurrence of cracks and peeling.

[0294] [Cold and hot cycle characteristics judgment criteria]

[0295] ○○: The number of cracks or peeling is 0 out of 5 samples

[0296] ○: The number of cracks or peeling is 1 to 2 out of 5 samples

[0297] ×: The number of cracks or peeling is 3 to 5 out of 5 samples

[0298] (4) Melting of the conductive part

[0299] The obtained conductive particles are spread on a Cu plate and heated under the conditions of 1) 135°C for 1 minute, 2) 155°C for 1 minute, 3) 160°C for 1 minute and 4) 200°C for 1 minute in an atmospheric atmosphere. The cross section of the conductive particles after heating is cut out by FIB-SEM using a focused ion beam (FIB). After cutting out the cross section, an electron microscope (SEM) is used to observe the melting state of the conductive part in the heated conductive particles near the junction between the conductive particles and the Cu plate to determine whether the conductive part is melted. It should be noted that when at least one of the following phenomena (1) and (2) is confirmed, it is determined that "the conductive part is melted". (1) When observed with an electron microscope (SEM), no boundary line is observed near the junction between the conductive particles and the Cu plate (interface portion). (2) In the elemental analysis of SEM-EDX when observing with an electron microscope (SEM), the Cu element diffuses from the Cu plate side to the inside of the conductive particles (especially the conductive part). In addition, when both the phenomenon (1) and the phenomenon (2) are not observed (a boundary line is observed along the interface between the conductive particle and the Cu plate, and the Cu element does not diffuse from the Cu plate side toward the inside of the conductive particle (particularly the conductive portion)), it is determined that "the conductive portion is not melted". It should be noted that when the conductive portion of the conductive particle contains the Cu element in advance, it is determined that the conductive portion is melted based on the phenomenon (1).

[0300] (5) Conductivity reliability (between upper and lower electrodes)

[0301] For the 20 connection structures obtained (the connection structures are connection structures prepared under the conditions of 1) 135°C, 2) 160°C, and 3) the melting point of the entire conductive part of each conductive particle + 20°C), the connection resistance between the upper and lower electrodes was measured by the 4-terminal method. In addition, according to the relationship of voltage = current × resistance, the connection resistance can be obtained by measuring the voltage when a certain current flows. The conduction reliability is determined according to the following criteria.

[0302] [Criteria for determining conduction reliability]

[0303] A: Connection resistance is 0.35Ω or less

[0304] B: Connection resistance is more than 0.35Ω and less than 0.41Ω

[0305] C: Connection resistance exceeds 0.41Ω

[0306] [Comprehensive judgment criteria for conduction reliability]

[0307] ○○○: The conduction reliability was rated A or B for all the connection structures prepared at 1) 135°C, 2) 160°C, and 3) the melting point of the entire conductive portion of each conductive particle + 20°C.

[0308] ○○: The connection reliability of the connection structure prepared at 1) 135°C was determined as C, and the connection reliability of the connection structure prepared at 2) 160°C and the connection structure prepared at 3) the melting point of the entire conductive portion of each conductive particle + 20°C was determined as A or B.

[0309] ○: In the connection structure prepared under the condition of 1) 135°C, the conduction reliability was judged as C, and in one of the connection structure prepared under the condition of 2) 160°C and the connection structure prepared under the condition of 3) the melting point of the entire conductive part of each conductive particle + 20°C, the conduction reliability was judged as C.

[0310] ×: The connection reliability was determined as C for all the connection structures prepared under 1) 135°C, 2) 160°C, and 3) the melting point of the entire conductive portion of each conductive particle + 20°C.

[0311] The configurations of the conductive particles and the results are shown in Tables 1 to 12 below.

[0312] [Table 1]

[0313]

[0314] [Table 2]

[0315]

[0316] [Table 3]

[0317]

[0318] [Table 4]

[0319]

[0320] [Table 5]

[0321]

[0322] [Table 6]

[0323]

[0324] [Table 7]

[0325]

[0326] [Table 8]

[0327]

[0328] [Table 9]

[0329]

[0330] [Table 10]

[0331]

[0332] [Table 11]

[0333]

[0334] [Table 12]

[0335]

[0336] Explanation of symbols

[0337] 1, 11, 21, 31…conductive particles

[0338] 2…Base material particles

[0339] 3, 13, 23, 33…conductive part

[0340] 13A, 23A…first conductive portion

[0341] 13B, 23B...second conductive portion

[0342] 23C…Third conductive part

[0343] 33a…protrusion

[0344] 34…Core material

[0345] 35…Insulating materials

[0346] 51…Connection structure

[0347] 52 ... first connection target component

[0348] 52a…first electrode

[0349] 53 ... second connection object component

[0350] 53a…second electrode

[0351] 54…Connection

Claims

1. A conductive particle comprising a substrate particle and a conductive portion disposed on a surface of the substrate particle, wherein: The conductive portion includes indium, When the conductive particles are heated under the condition of 160° C. in an air atmosphere for 1 minute, the conductive portion melts.

2. The conductive particle according to claim 1, wherein The conductive portion includes an alloy layer including an alloy of tin and indium.

3. The conductive particle according to claim 1 or 2, wherein The conductive portion has a conductive layer having a melting point of 200° C. or less, In 100 wt % of the conductive portion, the content of the conductive layer having a melting point of 200° C. or less is 10 wt % or more.

4. The conductive particle according to any one of claims 1 to 3, wherein The conductive portion has a layer containing copper or nickel, The substrate particles are in contact with the layer comprising copper or nickel.

5. The conductive particle according to claim 4, wherein The thickness of the layer containing copper or nickel is 0.05 μm or more and 2 μm or less.

6. The conductive particle according to any one of claims 1 to 5, wherein The conductive portion includes tin, The content of tin in 100 wt % of the conductive portion is 2 wt % or more.

7. The conductive particle according to any one of claims 1 to 6, wherein The conductive portion has a plurality of protrusions on its outer surface.

8. The conductive particle according to any one of claims 1 to 7, wherein When the X-ray diffraction spectrum of the conductive portion was measured, peaks existed in a region of 32° to 34° and a region of 55.5° to 57.5°.

9. The conductive particle according to any one of claims 1 to 8, wherein The outer surface of the conductive portion is surface-treated with flux.

10. The conductive particle according to any one of claims 1 to 9, wherein The particle diameter of the substrate particles is 0.5 μm or more and 100 μm or less.

11. A conductive material comprising: The conductive particle according to any one of claims 1 to 10, and Binder resin.

12. A connection structure comprising: a first connection target member having a first electrode on a surface thereof; a second connection target member having a second electrode on a surface thereof; and a connecting portion that connects the first connection target component and the second connection target component; The material of the connecting portion includes the conductive particles according to any one of claims 1 to 10, The first electrode and the second electrode are electrically connected via the conductive particles.

Citation Information

Patent Citations

  • Conductive particle, conductive material, and anisotropic conductive film

    JP2011134480A